An all-inkjet-printed flexible UV photodetector. Issue 25 (16th June 2017) - Dong, Yuhui; Zou, Yousheng; Song, Jizhong; Li, Jianhai; Han, Boning; Shan, Qingsong; Xu, Leimeng; Xue, Jie; Zeng, Haibo
Abstract : A flexible UV photodetector via all-inkjet printing was demonstrated, showing the feasibility of large-area and mask-free devices. Abstract : In this work, a novel concept of the all-inkjet-printed flexible photodetectors based on ZnO nanocrystals with high performance was proposed and demonstrated with emphasis on the influence of different post-treatments including UV light irradiation and high temperature annealing. The photodetectors based on UV-treated ZnO nanocrystal films exhibit a responsivity and an on/off ratio as high as 0.14 A W −1 and >10 3, respectively, which are better than the thermally treated devices. The high performance of ZnO nanocrystal-based photodetectors originates from unique band-edge modulation among the nanoparticles, where the existence of Schottky barriers leads to a low dark current and gives rise to a fast photoelectric response. The photodetector is capable of 500 bending cycles, and almost no degradation is observed. The as-obtained all-printable devices open up the possibility of fabricating a low-cost, solution processed, flexible, and large-area integrated optoelectronic sensor circuitry for future practical applications.